PELATIHAN PENGUNAAN APLIKASI CANVA UNTUK MENINGKATKAN LITERASI DIGITAL DALAM MEDIA PEMBELAJARAN GURU DI SD NEGERI 66 KOTA BENGKULU - Aam Amaliyah, Dela Puspita Sari; Dwi Anggreiny, Syerli feronica (STKIP Subang, 2025)
SD Negeri 66 Kota Bengkulu is a school located in Bengkulu City. This school is used to hold Canva Training to Improve the Quality of Teaching and Learning Activities at SDN 66 Kota Bengkulu. At SDN 66 Kota Bengkulu, there are 10 teachers. The priority issue during PKL (Field Work Practice) is the limited knowledge of teachers about Canva, therefore on the occasion of PKL (Field Work Practice) we took steps through a work program in the form of Canva Training to Improve the Quality of Teaching and Learning Activities at SDN 66 Kota Bengkulu, providing Canva presentation skills, allowing teachers to create interesting and easy-to- understand learning materials. Teachers will learn about the basics of Canva, Canva features, and interactive learning from Canva. Because not all teachers know Canva and understand more deeply than Canva itself. In responding to this, we took many steps so that teachers could discuss and solve the problems faced in making learning media. Then provide opportunities for teachers to practice making learning media with instructor guidance.